2023
DOI: 10.2174/1573403x18666220609123053
|View full text |Cite
|
Sign up to set email alerts
|

Machine-learning Algorithms for Ischemic Heart Disease Prediction: A Systematic Review

Abstract: Purpose: This review aims to summarize and evaluate the most accurate machine-learning algorithm used to predict ischemic heart disease. Methods: This systematic review was performed following PRISMA guidelines. A comprehensive search was carried out using multiple databases such as Science Direct, PubMed\ MEDLINE, CINAHL, and IEEE explore. Results: Thirteen articles published between 2017 to 2021 were eligible for inclusion. Three themes were extracted: the commonly used algorithm to predict ischemic hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Two studies used big data to reduce health disparities and improve the ability of health providers to meet predictable demand, 11,18 as well as to assess nursing leadership and decision-making. The results showed that big data can create new transformational leaders for nurses to efficiently use 21st-century health systems.…”
Section: Recommendation\considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies used big data to reduce health disparities and improve the ability of health providers to meet predictable demand, 11,18 as well as to assess nursing leadership and decision-making. The results showed that big data can create new transformational leaders for nurses to efficiently use 21st-century health systems.…”
Section: Recommendation\considerationsmentioning
confidence: 99%
“…Nurses must collect and analyze data in today's knowledge-based society. 10,11 In light of the evolution of nursing in the context of big data, big data centers for nursing science, advanced professional nursing databases, and a knowledge system structure are needed. 9 Big data can predict blueprints and patterns shared by thousands of people and evaluate multiple data sources collected by nurses and other health care professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Hani and Ahmad (2020) conducted a review of several machine learning algorithms that have the potential to detect ischemic heart disease. The authors present a comprehensive summary of various algorithms, including logistic regression, artificial neural networks, decision trees and support vector machines.…”
Section: Adoption Of Machine Learning In the Health Sectormentioning
confidence: 99%
“…For example, a study developed and validated a coronary artery disease-predictive machine learning model using electronic health records and assessed its probabilities as in silico scores for coronary artery disease in participants in two longitudinal biobank cohorts [10]. Another study applied an ensemble ML model for coronary disease prediction, using ML classi ers to predict heart disease [11].…”
Section: Introductionmentioning
confidence: 99%